2018
DOI: 10.4414/smw.2018.14602
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife radiosurgery for arteriovenous malformations: general principles and preliminary results in a Swiss cohort

Abstract: Radiosurgery is a safe and effective treatment modality for intracranial AVMs in selected cases. It can be used as upfront therapy or in the frame of a combined management. Obliteration rates are high, with minimal morbidity. The treatment effect is progressive and subsequent and regular clinical and radiological follow-up is needed to evaluate this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…In the case of a hemorrhagic event consensus can be easily reached to promote the earliest possible treatment of the vascular nidus, thus reducing the subsequent risk of new bleeding. Classical treatment options might include microsurgical resection 7 , endovascular approach 8,9 or stereotactic radiosurgery [10][11][12] . These treatment modalities can be performed stand-alone or combined, depending on the AVM architecture and the post-therapeutic evolution.…”
mentioning
confidence: 99%
“…In the case of a hemorrhagic event consensus can be easily reached to promote the earliest possible treatment of the vascular nidus, thus reducing the subsequent risk of new bleeding. Classical treatment options might include microsurgical resection 7 , endovascular approach 8,9 or stereotactic radiosurgery [10][11][12] . These treatment modalities can be performed stand-alone or combined, depending on the AVM architecture and the post-therapeutic evolution.…”
mentioning
confidence: 99%
“…Thirty-three (97%) studies were from single centres and one (3%) was multi-centre (Appendix 7 ). Thirteen (39%) studies were from North America [ 4 , 14 16 , 18 , 41 , 43 45 , 52 , 56 , 66 , 74 ], 12 (36%) from Asia [ 5 , 6 , 8 , 31 , 32 , 36 , 39 , 46 , 47 , 51 , 57 , 75 ] and 8 (24%) from Europe [ 2 , 24 , 35 , 49 , 54 , 58 , 65 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…All four studies had > 80% of total patients treated available for analysis at the end of follow-up. All studies were retrospective, except one which identified and followed consecutive patients prospectively (Appendix 7 ) [ 65 ]. Three studies (9%) were deemed moderate risk of reporting bias [ 6 , 8 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Para las MAVs más pequeñas, varios estudios han sugerido que la embolización previa es un factor predictivo negativo de la obliteración por SRS (14,31). Sin embargo, la reducción del tamaño por embolización aumentó la tasa de obliteración en las grandes MAV según lo informado por Veznedaroglu y colaboradores (32).…”
Section: Tratamiento Multimodalunclassified